Yield potential of hybrid castor bean plants in different plant densities in the off season in a stressful environment - Cruz, Brenda Juliana Elias; Alves, Danielle Cristina Lancarovici; Sá, Rogério Oliveira de; Viana, Ronaldo da Silva; Português, Português (Revista de Ciências Agroveterinárias, 2021)
The relevance of the castor bean plant in Brazil's agribusiness plan lies in the quality of the oil it produces. That is why, to improve its quality, there is interest in obtaining hybrid plants adapted to off-season growing conditions and with the appropriate characteristics for mechanized cultivation. This study was conducted to examine the premature growth of hybrid castor bean plants as a function of plant populations cultivated in the off season in the Nova Alta Paulista region of the state of São Paulo. A randomized complete block design with a 3x4 factorial arrangement, three hybrid castor bean plants (AGIMA 110204, MIA, and TAMAR) and four individuals per linear meter (2, 4, 6, and 8), was adopted, and four replications were performed for each treatment. The seeds were sown on April 12, 2017, at the UNESP/FCAT research farm in Dracena, São Paulo. Assessments on plant development and reproductive traits were made 138 days after emergence (DAE). The plants’ height, number of racemes per plant, 100-grain weight, and SPAD chlorophyll reading in the treatments resulted in similar averages. The TAMAR hybrid presented the highest insertion point for the primary raceme and, along with the MIA hybrid, produced the largest racemes. The stem diameter of all the hybrids presented a linear decrease as the plant population increased along the line the seeds were sown. The grain yields of the hybrids were 1,784 kg ha-1 (TAMAR), 1,659 kg ha-1 (AGIMA 110204), and 1,547 kg ha-1 (MIA).